Effects of carnosine on apoptosis, transient receptor potential melastatin 2, and betatrophin in rats exposed to formaldehyde - Akkoc, R. F.; Ogeturk, M.; Aydin, S.; Kuloglu, T.; Aydin, S. (Taylor & Francis Ltd, 2021)
We investigated the effects of exposure to formaldehyde on transient receptor potential melastatin 2, betatrophin, total oxidant status and total antioxidant status in rat liver and kidney tissues. We also investigated the effects of carnosine on formaldehyde treated animals. We used 28 male rats divided ramdomly into four groups of seven: untreated control group, carnosine treated group, formaldehyde treated group and formaldehyde + carnosine group. The experiment lasted for four weeks. Betatrophin levels in samples were measured uing the enzyme-linked immunosorbent assay, and total oxidant status and total antioxidant status were measured using REL assay diagnostic kits. We detected betatrophin and transient receptor potential melastatin 2 immunoreactivity using immunohistochemistry and assessed apoptosis using terminal deoxynucleotidyl transferase dUTP nick end labeling. The betatrophin and total antioxidant status levels decreased in kidney, liver and plasma following exposure to formaldehyde, while total oxidant status and terminal deoxynucleotidyl transferase dUTP nick end labeling positivity increased. Carnosine supplementation reversed histopathology and biochemical damage caused by formaldehyde. We suggest that carnosine treatment may be useful for protecting persons exposed to formaldehyde.
Keywords: Betatrophin; carnosine; formaldehyde; kidney; liver; transient receptor potential melastatin 2